Infrared, transient thermal, and electrical properties of silver nanowire thin films for transparent heaters and energy‐efficient coatings (Phys. Status Solidi A 1∕2017). Issue 1 (January 2017) - Bobinger, Marco; Angeli, Diego; Colasanti, Simone; La Torraca, Paolo; Larcher, Luca; Lugli, Paolo
Abstract : Due to the drastic rise in prices for indium over the past decade and the emergence of printed and flexible electronics, alternative materials such as metal nanowires and in particular silver nanowires (AgNWs) have drawn a lot of research interest, lately. Furthermore, the electro‐optical performance of random AgNW networks is gradually approaching the one of indium tin oxide. The article by Bobinger et al. (article no.1600466 ) presents spray‐deposited AgNW films for transparent heaters and as a low‐emissivity coating. For the simulation of the heaters, a Crank Nicolson method as well as a 3D percolation model that accounts for the temperature dependent wire‐towire (junction) resistances were developed. On the one hand, transparent heaters can be utilized for e.g. the fast defogging of car or airplane windows. On the other hand, depositing a low‐emissivity and transparent coating based on AgNW films to windows represents a cost‐efficient and facile method to save energy in civil buildings.